CONTENT ANALYSIS OF SPEAKING MATERIALS IN ENGLISH TEXTBOOK “BAHASA INGGRIS” USED BY THE TWELFTH GRADE OF SENIOR HIGH SCHOOL - Annisa Talcha Aritonang; Besral Besral; Darmayenti Darmayenti (UIN Imam Bonjol Padang, 2021)
This paper aimed to find out the degrees of linguistic supports, content based and affective supports, skill supports, and diversity and flexibility of speaking materials in ‘Bahasa Inggris’ used by the twelfth grade of senior high school. This was a descriptive research type with content analysis. The English textbook “Bahasa Inggris” published by the Indonesian Ministry of Education and Culture was the data. Theory of Dat Bao was used to analyze the data. Based on the analysis, the result of linguistic support shows 82 % which means “Good”. The result of content-based and affective support shows 87 % which means “fair”. The result of skill support shows 87 % which means “Good”. Diversity and flexibility shows the result 60 % which “Fair”. It is concluded that the speaking materials are not fully supported inspiration, imagination, creativity, and cultural sensibilities to satisfy learners with moments of inspiration, imagination, creativity, and cultural sensibilities, lack of spoken language characteristics, communication function and strategies, and variety of speaking materials. It implies that the materials should be elaborated to fulfill those criteria proposed by Bao’s.